The The Organic Nutrient and Chlorophyll-A Photopigment Variabilities During Coral Bleaching Indication in the Kapoposang Water Park (KWP) Spermonde Makassar Strait: Variabilitas Nutrien Organik dan Fotopigmen Klorofil-A Saat Indikasi Pemutihan Karang di Taman Wisata Perairan (TWP) Kapoposang, Spermonde Selat Makassar - Moh. Muhaemin Muhaemin; Vebby Versadasa; Taslim Arifin; Hafidzuddin Fihrin Fihrin (Journal of Tropical Fisheries Management, 2022)
Coral reefs at the Kapoposang’s Water Tourism Park (TWP) Spermonde Island have significant ecological and economical functions but prone to damage and even death. The proneness may occur by the effect of domestic activities or natural disaster. This study aimed to determine the distribution of biological (chlorophyll), chemical (nutrients included nitrate and phosphate) factors in ocean surface water, and to analyze the relationship of biological and chemical factors within coral bleaching event at TWP Kapoposang of Makassar Strait Spermonde. Primary and secondary data carried out during 2000-2020, and data analysis conducted on February to April 2021.The study used time-series data of the Indonesian monsoonal seasons for the last 18-years and Landsat satellite imagery data for coral mapping in 2000, 2005, 2015, and 2020. The results showed that the nutrients distribution tend to horizontally autoctonous and chlorophyll was varying within monsoonal seasons. Finally, nutrient and chlorophyll may be correlated with coral bleaching event at TWP Kapoposang of Spermonde Makassar Strait, respectively.